AB0028 Effect of genetic polymorphism of PTPN22 (protein tyrosine phosphatase non-receptor type 22) on progress and course of disease in familial mediterrenean fever. (23rd January 2014) - Seker, Z.; Kucuksahin, O.; Sahin, A.; Tuncalı, T.; Kinikli, G.; Turgay, M.
Abstract : Background: PTPN22 gene plays role in TCR signaling. PTPN22 gene polymorphism has been recently found to be related to several autoimmune diseases. Objectives: The aim of this study is to investigate the effect of PTPN22 gene polymorphisizm; which is related to several autoimmune disease; on the appereance and course of FMF which is also an autoinflammatory disease. Methods: In this study, the study group and control group were composed of 180 FMF patient and 184 healthy adults, respectively. The patients with autoinflammatory, chronic inflammatory or autoimmune diseases other than familial mediterranean fever were excluded. A variant of PTPN22 gene, 1858 C/T, was examined by PCR-RFLP method in DNA samples taken from participants at study and control groups. Results: The mean age of 180 patients was 38.2 (SD ±11.6) and the age distribution was 16-81. The numbers of females and males at study group were 112 (% 62.2) and 68 (% 37.8), respectively. The mean age of 184 healthy adult participiants at control group was 32.9 (SD ± 9.2) and age distribution was 18-58. The numbers of females and males at control group were 112 (% 62.2) and 68 (% 37.8), respectively. In the study group, PTPN22 gene polymorphism was studied in 177 of total 180 participants (product? couldn't be obtained in blood samples of 3 patients). It was found that 168/177 (95%) were homozygotic (G/G polymorphism), 8/177 (%4.5) were heterozygotic (G/A polymorphism) and 1/177 (%0.5) was polymorphic homozygotic (A/A polymorphism). In the control group, PTPN22 gene polymorphism was studied in 180 of total 184 participants (product? couldn't be obtained in blood samples of 4 patients). It was found that 174/180 (96, 7%) were normal homozygotic (G/G polymorphism), 5/180 (%2.8) were heterozygotic (G/A polymorphism) and 1/180 (%0.5) was polymorphic homozygotic (A/A polymorphism). Conclusions: We couldn't find statistically significant datas between patients with FMF and healthy adults in terms of PTPN22 gene polymorphism. We also determined that PTPN22 gene polymorphism showed no statistically significant relationship with disease severity and clinical features of FMF. Even if it was not statistically significant, we determined that prolonged arthralgia and pericarditis was not present in the patients with PTPN22 G/A and A/A polymorphisms. More studies are needed in order to evaluate the relationship of PTPN22 gene polymorphism with FMF. References: Onen F. Familial mediterranean Fever. Rheumatol Int. 2006 Apr; 26 (6): 489-96 Ben-Chetrit E, Levy M. Familial Mediterranean fever. Lancet. 1998 28;351:659-664 Wu J, Katrekar K, Honigberg LA, Smith AM, ConnMT, TangJ, Jeffrey D, Mortara K, Sampang J, Williams SR, Buggy J, Clark JM. Identification of substrates of human protein tyrosine phosphatase PTPN22. J Biol Chem 2006;281: 11002–11010. Torkel Vang, Ana V.Miletic, Nunzıo Bottını, Tomas Mustelın. Protein tyrosine phosphatase PTPN22 in human autoimmunity. Autoimmunity, September 2007; 40 (6): 453–461 Disclosure of Interest: None Declared